Polski pazdziernik '56 : poczatek drogi - Bombicki, Maciej Roman, 1948- (Poznan : Polski Dom Wydawniczy "Lawica", 1993)
A study on the begining of the fall of communism in Poland, in October 1956.
Includes bibliographical references and index.
Keywords: Poland -- History -- Uprising, 1956 -- Sources; Anti-communist movements -- Poland -- History -- Sources